REFUND OF FINANCIAL LOSS IN THE CRIME OF CORRUPTION LINKED WITH ARTICLE 81 OF LAW NUMBER 8 YEAR 2010 ON CRIME PREVENTION AND COMBATING MONEY LAUNDERING - Muhd Nafan (Awang Long Law Review, 2022)
Returning state financial losses is the focus of the corruption law, especially in the case of money laundering crimes committed by state officials to deceive law enforcement officials in examining the assets of public officials. One way to return state assets is to seize or confiscate assets suspected of being the result of corruption or money laundering. Money laundering is an attempt to hide or disguise the origin of money/funds or wealth resulting from a criminal act through various financial transactions so that the money or assets appear as if they came from legal/legal activities. The research method used in this study is a normative juridical approach with the sources of legal materials used are primary sources of legal materials and secondary sources of legal materials. The technique of collecting legal materials uses a literature study of listening techniques and the technique of analyzing legal materials using qualitative analysis techniques. The results of the study indicate that the implementation of the return of state financial losses on corruption is related to Article 81 of Law Number 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering. can be done by tracking, freezing, confiscation, confiscation and repatriation.